Jogos e psicanálise: uma leitura de elementos da cultura ocidental em Alice Madness Returns - Zansavio, Winna Hita Iturriaga (2015)
The research reflects about digital games as a product and object of culture construing the elements of its constitution from the psychoanalysis point of view as happened previously in the literature, the theater and the cinema. It construes its methodological course from Arlete dos Santos Petry reflection in "Heavy Rain or What We can Experience with Narratives in Digital Games" (2011), in which digital games and their constituent structures are thought of as enablers agents of subject emotional experiences and fundamental reflections, both for the players and for developers. I will present the concepts and content defined by Freudian Psychoanalysis base that may be present in digital games, applying them on the elements present in a digital game that starts as the point of the work of Lewis Carroll, the game "Alice Madness Returns". Based on the connexion between the concepts organized by Psychoanalysis and the development of the game performed by the developer/author, the search goes so far as to consider the elements present in the digital games as symbolic structures that are part of culture and human development. It concludes with the need for further study of relations between games, culture, design and narrative with the Psychoanalysis knowledges about art in general